Self-perceived burden in elderly patients with chronic co-morbidities: a latent profile analysis - Chen, Qiqi; Jia, Yan; Li, Hui; Lv, SiLu; Du, Tianjiao; Feng, Achong (Frontiers in Psychology, 2025)
ObjectiveThis study aims to identify latent categories and characteristics of self-perceived burden among elderly patients with chronic comorbidities through latent profile analysis, and to analyze influencing factors across different latent categories.MethodsThis study adopted a convenience sampling method, this research enrolled 632 hospitalized elderly patients with chronic comorbidities as study participants from January to April 2024. Data collection utilized surveys including general information questionnaires, the self-Perceived burden scale, the medication knowledge scale for elderly chronic disease Patients, and the technophobia scale. Latent profile analysis was conducted to characterize the self-perceived burden among respondents, with one-way ANOVA and logistic regression analysis employed to explore influencing factors across different categories.ResultsThis study collected 611 valid questionnaires. Based on potential profile analysis, the self-perceived burden of elderly patients with chronic diseases was categorized into three groups: moderate, low, and high symptom groups, accounting for 43.54, 36.49, and 19.97%, respectively. Univariate analysis revealed that factors such as status of occupational, personal monthly income, caregivers, residential mode, medical insurance type, daily exercise duration, course of disease, times of hospitalizations, self-rated sleep status, medication literacy and technology anxiety impact the self-perceived burden of chronic comorbidities across different categories.ConclusionOlder adult patients with chronic comorbidities demonstrated heterogeneity in latent profiles of self-perceived burden, with those experiencing moderate burden accounting for the highest proportion. Medication literacy and technology-related anxiety significantly influenced self-perceived burden. Healthcare professionals should develop targeted health education programs and early intervention strategies to reduce patients’ self-perceived burden levels.